2020
DOI: 10.1093/cid/ciaa006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pregnancy on the Pharmacokinetics of Total and Unbound Dolutegravir and Its Main Metabolite in Women Living With Human Immunodeficiency Virus

Abstract: Background Pharmacokinetic and efficacy data on dolutegravir in pregnant women living with human immunodeficiency virus (HIV) are still limited but needed to support its use as one of the preferred antiretroviral agents. Methods Within the multicenter Pharmacokinetics of ANtiretroviral agents in HIV-infected pregNAnt women (PANNA) study, pregnant women living with HIV and using dolutegravir once daily (50 mg, with food) under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 20 publications
6
38
0
Order By: Relevance
“…Combined with the results from the sensitivity analysis on UGT1A1 induction (Fig. S4), this finding emphasizes that UGT1A1 induction may be lower than expected here and that changes in the fraction unbound are, at least for DTG, the main driver of increased total clearance which is consistent with recent findings in the literature [46]. The PK of RAL was generally well predicted in pregnant, non-laboring women (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Combined with the results from the sensitivity analysis on UGT1A1 induction (Fig. S4), this finding emphasizes that UGT1A1 induction may be lower than expected here and that changes in the fraction unbound are, at least for DTG, the main driver of increased total clearance which is consistent with recent findings in the literature [46]. The PK of RAL was generally well predicted in pregnant, non-laboring women (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Clinical and pre-clinical studies showed high levels of transplacental transfer of INSTI drugs ( Schalkwijk et al, 2016 ; Mulligan et al, 2018 ; Mandelbrot et al, 2019 ; Waitt et al, 2019 ; Bollen et al, 2021 ; Bukkems et al, 2021 ). Studies of DTG have found high placental transfer of DTG from mother to fetus with median cord blood to maternal blood drug level ratios from 1.21 up to 1.29 ( Schalkwijk et al, 2016 ; Mulligan et al, 2018 ; Mandelbrot et al, 2019 ; Waitt et al, 2019 ; Bollen et al, 2021 ). Further, DTG was also found to accumulate in the fetus with noted prolonged elimination of drug from infants after birth ( Mulligan et al, 2018 ; Waitt et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For boosted ARVs, if the key mechanism of lower exposures during pregnancy is due to lower exposures of PK boosters (ritonavir or cobicistat), then a dose increase of the PK booster rather than a dose increase of the boosted ARV (eg, protease inhibitor) can potentially be considered to achieve the target concentration correlating with efficacy. 35 When recommending a dose increase during pregnancy, an overall risk-benefit assessment should be considered. In Bonafe et al, 36 pregnant individuals assigned to receive an increased dose of lopinavir/ritonavir had a higher rate of diarrhea as compared to those who were using lopinavir/ritonavir at the time of randomization and who were assigned to receive the conventional dose.…”
Section: Translation Of the Results Into Clinical Recommendationsmentioning
confidence: 99%